A Rare Case of Pulmonary Tuberculosis Masquerading as Laryngeal Tuberculosis or Malignant Manifestation - Madolangan, Jamaluddin; Fiqran, Muhammad; Affan, Muhammad; Herman, Bumi (Faculty of Medicine Universitas Airlangga, 2024)
Introduction: Laryngeal tuberculosis (LTB) is usually accompanied by pulmonary tuberculosis (TB) involvement. Misdiagnosis often occurs because the symptoms are non-specific and resemble laryngeal malignancy. We reported a rare condition of pulmonary TB masquerading as larynx abnormalities such as malignant manifestations. Case: A 59-year-old man presented with a main complaint of prolonged hoarseness without clinical respiratory complaints. The patient additionally reported coughing as a symptom while receiving medical treatment in the hospital. A computed tomography (CT) scan of the neck without contrast revealed a glottic tumor invading the vocal cord – T3N2cMx. Laryngoscopy examination revealed T1-T1 tonsils. The pharyngeal mucosa was slightly hyperemic. The arytenoids and epiglottis were less hyperemic. There was no edema, the left vocal fold was paralyzed, could not be adducted, and there was a lump. The glottis rima gap was narrow, size 3–4 mm, and the mass could not be evaluated. Chest X-ray examination was normal, but rapid molecular tests of TB detected very low Mycobacterium tuberculosis (MTB) levels. The patient was treated with anti-TB treatment (ATT) according to body weight. An evaluation was performed after 2 weeks, and the patient's clinical and physical condition improved. Conclusion: Pulmonary TB patients in endemic countries can have clinical manifestations such as LTB or laryngeal malignancy in 1% of cases. The prognosis for LTB with pulmonary T involvement is quite good with ATT administration.